2021
DOI: 10.35580/lageografia.v19i3.14718
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Discovery Learning pada Pembelajaran Geografi untuk mengurangi Miskonsepsi Peserta Didik

Abstract: This study aims to: 1) find out how the picture of learning outcomes of students by using the Discovery The purpose of this study was to determine the application of the Discovery Learning learning model and the effect of the Discovery Learning learning model in overcoming the misconception of atmospheric material. Data was collected in February-March 2020. The research design method used was an experimental method with the Pretest and Posttest control group design. In this study conducted in two classes, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
1
0
4
Order By: Relevance
“…Discovery learning models applied to control classes tend to be more effective than constructivist learning models. The results of the study showed that there was a significant difference in support in the experimental group given the Discovery Learning model compared to the control group regarding the average academic achievement, learning retention score, and perception of skill score inquiry, both at the cognitive and affective level (Fitri & Derlina, 2015;Indriana et al, 2021). Discovery learning model influences student achievement in knowledge and skills in salt hydrolysis materials (Kurnianto & Masykuri, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Discovery learning models applied to control classes tend to be more effective than constructivist learning models. The results of the study showed that there was a significant difference in support in the experimental group given the Discovery Learning model compared to the control group regarding the average academic achievement, learning retention score, and perception of skill score inquiry, both at the cognitive and affective level (Fitri & Derlina, 2015;Indriana et al, 2021). Discovery learning model influences student achievement in knowledge and skills in salt hydrolysis materials (Kurnianto & Masykuri, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Kesulitan juga dialami oleg guru disebabkan waktu jam pembelajaran yang kurang agar dapat menggali potensi siswa dalam mengatasi permasaahan geosfer. Kesulitan pembelajaran geografi juga ditambah saat masa pandemik (Indriana et al, 2021).…”
Section: Pendahuluanunclassified
“…Geografi sangat penting bagi siswa karena menghubungkan mereka dengan lingkungan mereka. Geografi sendiri berkaitan dengan bumi, matahari, alam semesta, cuaca, iklim, spesies di permukaan bumi, dan proses yang terjadi kemudian (geosfer) (Hasriyanti, 2019;Indriana et al, 2021). Lebih lanjut, (Pratiwi et al, 2021) menjelaskan bahwa pada mata pelajaran geografi perlu menguasai jumlah materi pembelajaran untuk berbagai fenomena spasial dan adanya materi yang sulit dipahami tanpa melihat fenomena yang sebenarnya di lapangan.…”
Section: Pendahuluanunclassified